Play Therapy dengan Media Puzzle untuk menurunkan Gangguan Pemusatan Perhatian/Hiperaktivitas (GPPH) pada Anak Attention Deficit Hyperactivity Disorder (ADHD) - Anggita Putri Nur Sholichah; Muhimmatul Hasanah (JURNAL PSIMAWA, 2023)
Play therapy can improve concentration, reduce symptoms (increase attention and reduce impulsive and hyperactive behavior), and reduce deviant behavior in ADHD children. The more often play therapy interventions are carried out, the more positive changes that can be made that can last for a long time or even be permanent. This research uses a type of experimental research consisting of pre-test and post-test. The subject experienced a decrease in GPPH scores after being given Play Therapy with Puzzle Animal media. The subject experienced a decrease in score of 4 from a pretest result of 45 to a score of 41. ADHD after being given Play Therapy treatment with Puzzle Animal. The subjects in this research were Kaf. From the results of this report, it can be concluded that Play Therapy using Puzzle Animal media is able to reduce ADHD in Attention Deficit and Hyperactivity Disorder (ADHD) children.